1986
DOI: 10.1042/cs0710271
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thyroid dysfunction on serum calcium in the rat

Abstract: Serum calcium was measured under different circumstances of thyroid dysfunction in male Sprague-Dawley and female Wistar rats. After induction of hypothyroidism with 131I and propylthiouracil, serum calcium fell from a control value of 2.43 +/- 0.08 mmol/l to 2.07 +/- 0.08 mmol/l (P less than 0.01). Thyroid hormone replacement therapy in hypothyroid rats caused a return of serum calcium to control values (2.09 +/- 0.04 mmol/l to 2.41 +/- 0.02 mmol/l, P less than 0.01). Treatment of normal rats with thyroid hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
9
0

Year Published

1987
1987
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…Gammage reported negative correlation of serum phosphorous with TSH. The study of Kavitha et al showed significant positive correlation (p< 0.003) with TSH in overt hypothyroidism [22].…”
Section: Discussionmentioning
confidence: 99%
“…Gammage reported negative correlation of serum phosphorous with TSH. The study of Kavitha et al showed significant positive correlation (p< 0.003) with TSH in overt hypothyroidism [22].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies carried out on serum calcium and phosphorus levels in thyroid disorders had conflicting results. Some studies reported normal levels [19,20], while others reported decreased serum calcium and phosphorus levels in hypothyroidism [21]. Vitamin D has been reported to be deficient in the hypothyroid patients [32].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies carried out on serum calcium and phosphorus levels in thyroid disorders have had conflicting results. Some studies have reported normal levels [19,20], while others have reported decreased serum calcium and phosphorus levels in hypothyroidism [21]. Hyperthyroidism causes excessive excretion of calcium and phosphorus in urine because the high serum calcium levels in hyperthyroidism have a negative feedback on the secretion of parathyroid hormone which has a role in calcium and phosphorus absorption [22].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, in the blood serum of thyrotoxicosis patients who have undergone 131 I treatment the reduction in the thyroxin level was accompanied also by a reduction in the calcitonin level (Bayaraktar, 1990). In such patients there was a reduction in the stability of reaction to the induction of high doses of calcium, thus giving evidence of a breakdown in calcium homeostasis (Gammage, 1986). It is obvious that this is a direct consequence of radiation damage and the breakdown in the production of calcitonin by the C-cells which have direct contact with the thyrocytes (Bayraktar, 1990;Tzanela et al, 1993).…”
Section: Discussionmentioning
confidence: 99%